Study of some γ-ray attenuation parameters for new shielding materials composed of nano ZnO blended with high density polyethylene - Alsayed, Zainab; Badawi, Mohamed; Awad, Ramadan; Thabet, Abouzeid; El-Khatib, Ahmed (Nuclear technology & radiation protection, 2019)
The extensive utilization of radiation is rapidly developing worldwide involving abundant fields like medical, industrial, research, and nuclear facilities. This makes the need for studying radiation shielding materials and their properties more urgent than ever. In the present study, bulk and nano ZnO were mixed by the same ratio each time (10, 20, 30, and 40 wt.%), with high-density polyethylene as a polymer matrix and characterized by X-ray diffraction. The results confirmed the good dispersion of bulk and nano ZnO particles within the polymer matrix. The prepared composite samples were used in different thicknesses as gamma ray shielding materials, and the heaviness was calculated and compared to lead. Using HPGe detector at specific energies (59.53, 356.01, 661.66, 1173.33, and 1332.50 keV) for different radioactive point sources (241Am, 133Ba, 137Cs, and 60Co), the mass attenuation coefficient for the samples was measured experimentally. Depending upon the obtained values, the linear attenuation coefficient, half-value layer, tenth value layer, heaviness and relaxation length were estimated. Using the XCOM database, the values of linear attenuation coefficient, mass attenuation coefficient, and other parameters were calculated theoretically for the bulk ZnO blended with high-density polyethylene. The obtained results were compared to the experimental values for nano and bulk ZnO blended with high density polyethylene. The radiation shielding behavior of nano ZnO blended with high density polyethylene was found to be more promising and efficient for radiation protection against gamma ray. nema